Reactive-active power control for grid-connected PV arrays to enlarge the hosting capacity in a low voltage distribution system - Hamza Abunima,; Jiashen Teh,; Hussein Jumma, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The stochastic behavior of solar radiation is one of the challenges faced by increasing the hosting capacity of the photovoltaic (PV) power. At times of exceptional high PV power output, unacceptable voltage rise could happen at PV system terminals. Violating the voltage threshold adversely affect the power quality and security at the customer sides. In order to avoid this, the PV system is normally disconnected during high PV power output, thus causing losses in power generated. Local control approaches have been introduced as a measure to overcome this issue by using only the inverter. One of these approaches is to control the reactive power output of a PV unit in order to suppress the voltage rise without ceasing the PV system. The results from this paper have shown that the existing reactive power control (RPC) approach is unable to suppress this voltage rise effectively in case of low X/R ratio. Active power curtailment (APC) is another approach that results in remarkable power losses. Hence, this paper proposes a methodology that combines both RPC and APC approaches to limit the voltage rise in a low voltage distribution feeder. The effectiveness of the proposed methodology have been examined and demonstrated in this paper. The obtained results show the superiority of the proposed methodology over the conventional approaches, which enlarges the hosting capacity for PV power penetration in a low voltage distribution system.